Present state of archaeometric and technological research on Neolithic pottery in Northern Croatia - Težak-Gregl, Tihomila; Burić, Marcel (2007)
The presentation brought the present state of archaeometric and technological research done until now on the neolithic pottery of Starčevo, Korenovo and Sopot Culture, distributed in the Northern Croatia.
Projekt MZOS
ENG